Clinical Aspects of Renal Artery Variations - HarjeetKaur Daisy Sahni, Richa Gupta KunalChawla Anjali Aggarwal Tulika Gupta (International Journal of Scientific Research and Management (IJSRM), 2017)
Amongst large number of anatomical variations in the vascularization of the kidney, the most common variation is the occurrence of multiple renal arteries. The arteries play an important role in the circulatory system as they carry a large portion of blood to the kidneys. Due to very high incidence of such variations reported by previous studies, current study was conducted to observe incidence of such variations in renal arteries among North West Indian population. Accessory renal arteries, which are the most common and clinically important variations of the renal circulatory system, are encountered in approximately one third of anatomic dissection series.In the current study, the formalin fixed forty cadavers were dissected in department of Anatomy, PGIMER, Chandigarh. Then, kidneys along with their arteries were explored and the morphological variations of renal arteries were observed.Authors in current study observed maximum incidence of origin of RA at the level of L1 (right side - 86%; left side - 80%). It was observed that in 70% of the cases, right renal artery ostium was lying cranial to that of left renal artery, in 24% cases, left renal artery ostium cranial to that of right ostium and in 6% both the ostia were seen lying at symmetrical levels. In all the cases, diameter of accessory renal arteries was found to be narrower than that of main renal artery.In one case, we observed a variation in the arrangement of structures at hilum of kidney. Renal vein was seen compressed between the branches of renal artery. Our results present a significant high variation in occurrence of different forms of multiple renal arteries in Indian population in comparison to other population